Film Animasi Sosial dan Keaktifan Siswa dalam Pembelajaran IPS di SD Inpres Borisallo Kabupaten Gowa - Nur Indah Sari; Jamaluddin Arifin; Rubianto Rubianto (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
Social Study learning will show satisfactory results, if the teacher is able to choose the right media in teaching. So that students have an interest and have high activity to ask in accordance with the expectations of students and teachers, one of which is in the process of delivering social studies lessons using animated film media to improve student learning. Social animated film media is one of social studies teaching media that is used to explain some natural and other phenomena. With this media students know more and are clear about the concepts of social studies learning and its content. Likewise students in the teaching-learning process need to get the learning process so that their learning achievement increases. This study describes social animated films and students' activeness in social studies learning. The results of this study through observation, interviews with fourth grade teachers and fourth grade students at SDI Borisallo, Gowa Regency resulted that students liked learning by using social animated films rather than not using them. They also have a high curiosity about new things and find it interesting after carrying out learning with the help of social animated films. Students also rarely use learning media in social studies lessons, so that if the teacher uses media in learning, students will feel happy and more enthusiastic and active in the teaching and learning process.